2022
DOI: 10.3389/fpubh.2022.836985
|View full text |Cite
|
Sign up to set email alerts
|

Serum Angiopoietin-Like Protein 4: A Potential Prognostic Biomarker for Prediction of Vascular Invasion and Lymph Node Metastasis in Cholangiocarcinoma Patients

Abstract: Cholangiocarcinoma (CCA) is a tumor arising from cholangiocytes lining the bile ducts. Vascular invasion and lymph node metastasis are important prognostic factors for disease staging as well as clinical therapeutic decisions for CCA patients. In the present study, we applied CCA sera proteomic analysis to identify a potential biomarker for prognosis of CCA patients. Then, using bioinformatics tools, we identified angiopoietin-like protein 4 (ANGPTL4) which expressed highest signal intensity among candidate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Moreover, ANGPTL4 can participate in tumor energy metabolism in different NSCLC cells and affect cell proliferation through this process [82]. High expression of ANGPTL4 predicts adverse clinical outcomes in tumors, such as renal clear cell carcinoma, cholangiocarcinoma, melanoma, bladder cancer, and oral cancer [83][84][85][86][87]. In this study, ANGPTL4 was a high-risk gene that increased with tumor progression, suggesting a reduced survival rate and poor prognosis in LUAD patients.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, ANGPTL4 can participate in tumor energy metabolism in different NSCLC cells and affect cell proliferation through this process [82]. High expression of ANGPTL4 predicts adverse clinical outcomes in tumors, such as renal clear cell carcinoma, cholangiocarcinoma, melanoma, bladder cancer, and oral cancer [83][84][85][86][87]. In this study, ANGPTL4 was a high-risk gene that increased with tumor progression, suggesting a reduced survival rate and poor prognosis in LUAD patients.…”
Section: Discussionmentioning
confidence: 57%
“…cervical (14), colorectal (15), gastric (16), and breast (36) cancer. We previously reported overexpression of ANGPTL4 in CCA tissues and serum from patients, suggesting that it may be a marker for poor prognosis of CCA (17). San et al demonstrated that knockdown of ANGPTL4 reduced the death of CCA cells (18).…”
Section: Figure 4 Correlation Of Gene-expression Levels Between Angio...mentioning
confidence: 94%
“…In-solution tryptic digestion. Five micrograms of total protein isolated from cell lysates of ANGPTL4-silenced and scrambletreated control cells were digested according to the method developed by the Functional Proteomics Technology Laboratory, National Center for Genetic Engineering and Biotechnology, National Science and Technology Development Agency, Thailand (17). Briefly, samples were completely dissolved in 10 mM ammonium bicarbonate then 5 mM dithiothreitol in 10 mM ammonium bicarbonate was used to reduce disulfide bonds at 60˚C for 1 h and 15 mM iodoacetamide in 10 mM ammonium bicarbonate was used for alkylation of sulfhydryl groups at room temperature for 45 min in the dark.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation